2013
DOI: 10.1158/1078-0432.ccr-12-2982
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Immunostimulatory Monoclonal Antibodies in Combination Strategies for Melanoma and Other Tumor Types

Abstract: Modulation of the immune system by targeting coinhibitory and costimulatory receptors has become a promising new approach of immunotherapy for cancer. The recent approval of the CTLA-4-blocking antibody ipilimumab for the treatment of melanoma was a watershed event, opening up a new era in the field of immunotherapy. Ipilimumab was the first treatment to ever show enhanced overall survival (OS) for patients with stage IV melanoma. However, measuring response rates using standard Response Evaluation Criteria in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 81 publications
2
98
0
2
Order By: Relevance
“…3). It is still controversial whether such adverse events correlate with clinical benefit (15)(16)(17). Some authors hold that the development of an irAE may not be predictive of ipilimumab activity (15 melanoma, who received the treatment, no correlation between toxicity and efficacy was found.…”
Section: Building On a Story Of Successmentioning
confidence: 99%
“…3). It is still controversial whether such adverse events correlate with clinical benefit (15)(16)(17). Some authors hold that the development of an irAE may not be predictive of ipilimumab activity (15 melanoma, who received the treatment, no correlation between toxicity and efficacy was found.…”
Section: Building On a Story Of Successmentioning
confidence: 99%
“…3,6,8,16,17 In a study of 95 patients treated with ipilimumab, Simeone et al reported that decreased levels of lactate dehydrogenase (LDH), c-reactive protein (CRP), and circulating regulatory T cells (Treg) were all significantly associated with clinical response to ipilimumab and improved survival. 3,24 Large multicenter studies will be required to validate these tests, and others, so that care for patients with advanced melanoma can be tailored appropriately.…”
Section: 22mentioning
confidence: 99%
“…In addition, as for many other (immuno)therapeutic interventions, it will be crucial to identify biomarkers that reliably predict the propensity of individual patients to respond to peptide-based anticancer vaccines. [269][270][271][272][273] Time will tell whether these avenues are those that lead to the approval of peptide vaccination by international regulatory agencies for use in cancer patients.…”
Section: Discussionmentioning
confidence: 99%